Impact of Samurdhi program on poverty alleviation: An empirical investigation of Samurdhi Bene ciaries in Kopay DS Division in Jaffna District - Thavarasasingam, H.; Balagobei, S. (Sabaragamuwa University, 2020)
The aim of this study is to investigate the impact of Samurdhi Program on poverty alleviation in Kopay DS Division. Two hundred questionnaires were issued to the Samurdhi bene ciaries of Kopay DS division, in Ja na district, Sri Lanka Such as Kopay north (J/262),Irupalai South (J/257), Urelu (J/267) and Urumpirai south (J/265) divisions. Urelu (J/267) and Urumpirai south (J/265) divisions. Out of which, 177 questionnaires only could be collected. Hence, 177 Samurdhi bene ciary families were incorporated as samples. Correlation analysis and multiple linear regression analysis were used to analyze the data and examine the hypotheses by using the SPSS. The adjusted R2 0.250 for the model implies that approximately 25% of the total variance in poverty alleviation can be determined by all dimensions of Samurdhi program as the independent variable in this model. Further, the model reveals that the remaining 75% of variability was not explained in this model. In this study the ndings revealed that there is a signi cant impact of Samurdhi program on poverty alleviation. Microcredit has a positive and signi cant impact on poverty alleviation. Livelihood activity has an insigni cant impact on poverty alleviation. Welfare has a positive and signi cant impact on poverty alleviation. Based on the ndings the researcher can conclude that Microcredit and welfare activity is e ectively worked, and livelihood activity needs to improve itself.
Keywords: Income level; Livelihood activity; Micro credit; Poverty alleviation; Samurdhi Program; Welfare activity